APPLICATION TRAINING FOR STRENGTHENING CHARACTER EDUCATION AT INTAN PERMATA EBAN VOCATIONAL MIDDLE SCHOOL - Fransiskus Keraf; Marsianus Falo (Universitas Majalengka, 2022)
Character education is an effort carried out by the government in realizing the essence of good citizens. Efforts to realize this can be obtained through devotion carried out in training applications for strengthening educational characters. This goal is to provide an understanding for schools to implement programs to improve character education. The implementation of the activity consists of four stages, namely preparation, survey and determination, implementation, evaluation and follow-up. This activity uses demonstration and example methods, namely providing demonstrations of patterns of application of character education in schools through habituation and learning in class as well as exemplifying its types. This training resulted in two types of applications to strengthen the character of education, namely through habituation and learning in the classroom. In addition to giving presentations, participants also gain knowledge about the process of applying it in daily activities in the school environment. Keywords: Training., Application., Character Education.